2022
DOI: 10.5194/hess-26-1659-2022
|View full text |Cite
|
Sign up to set email alerts
|

The role of morphology in the spatial distribution of short-duration rainfall extremes in Italy

Abstract: Abstract. The dependence of rainfall on elevation has frequently been documented in the scientific literature and may be relevant in Italy, due to the high degree of geographical and morphological heterogeneity of the country. However, a detailed analysis of the spatial variability of short-duration annual maximum rainfall depths and their connection to the landforms does not exist. Using a new, comprehensive and position-corrected rainfall extreme dataset (I2-RED, the Improved Italian-Rainfall Extreme Dataset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…As shown in other studies on the Italian peninsula and Italian Alps there is not always a consistent relationship between topography and sub-daily rainfall intensity and local factors play a large role in varying this relationship (Formetta et al, 2022;Mazzoglio et al, 2022). At durations below 1-h a reverse-orographic effect of decreasing intensity with elevation is well documented (Avanzi et al, 2015;Marra et al, 2021) but for durations between 2 and 6-h the effect is less clear, with intensity sometimes enhanced but not consistently (Formetta et al, 2022;Mazzoglio et al, 2022). Coastal effects may also be important for short-duration extremes (Marra et al, 2022) but this effect is not obvious here.…”
Section: -H Indices Comparisonmentioning
confidence: 88%
“…As shown in other studies on the Italian peninsula and Italian Alps there is not always a consistent relationship between topography and sub-daily rainfall intensity and local factors play a large role in varying this relationship (Formetta et al, 2022;Mazzoglio et al, 2022). At durations below 1-h a reverse-orographic effect of decreasing intensity with elevation is well documented (Avanzi et al, 2015;Marra et al, 2021) but for durations between 2 and 6-h the effect is less clear, with intensity sometimes enhanced but not consistently (Formetta et al, 2022;Mazzoglio et al, 2022). Coastal effects may also be important for short-duration extremes (Marra et al, 2022) but this effect is not obvious here.…”
Section: -H Indices Comparisonmentioning
confidence: 88%
“…As already mentioned in the introduction, trying to find the best rainfall-elevation relation for a particular area at the event-based scale is not straightforward, confirming the difficulties encountered by [53,54]. In fact, the spatial and temporal variability of the precipitation, especially if the orographic effect can trigger convective thunderstorms, generally does not follow a linear rainfall-elevation function [21,27].…”
Section: Eventmentioning
confidence: 89%
“…Unfortunately, this relation cannot be generalized to all seasonal periods and it is generally not valid during the summer when thunderstorm convection generally occurs [53]. A confirmation was made by the authors of [54], who carried out a study for the whole Italian Peninsula based on the Improved Italian-Rainfall Extreme Dataset (I2-RED) [62]. These authors have reported that it is rather difficult to find a generalized orographic precipitation gradient, although their analysis has not given any statistical evidence of a correlation between rainfall and elevation for the Italian Peninsula considering extreme rainfall events.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A discussion of the overall spatial and temporal variability of the rainfall extremes is available in Mazzoglio et al (2020Mazzoglio et al ( , 2022aMazzoglio et al ( , b, 2023. What is useful to comment on here is the result of the spatial averaging of the parameters a and n at the catchment scale (Fig.…”
Section: Extreme Rainfall Catchment Attributesmentioning
confidence: 99%